PENGARUH LINGKUNGAN KERJA FISIK DAN PELATIHAN TERHADAP KINERJA KARYAWAN PADA PT ANUGRAH SUKSES METAL INDONESIA DI PASAR KEMIS KABUPATEN TANGERANG - Aliansah, Muhammad; Supardi, Yusuf (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Abstrak. The purpose of this research is to determine the effect of the physical work environment and training on employee performance at PT Anugrah Sukses Metal Indonesia in Pasar Kemis, Tangerang Regency. The method used is quantitative. The sampling technique used saturated sampling, namely 84 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The results of this research are that the physical work environment has a significant effect on employee performance with a coefficient of determination value of 48.6% and the hypothesis test obtained t count > t table or (8,800 > 1,989). Training has a significant effect on employee performance with a coefficient of determination value of 51.3% and hypothesis testing obtained t count > t table or (9.298 > 1.989). The physical work environment and training simultaneously have a significant effect on employee performance with the regression equation Y = 7.409 + 0.380X1 + 0.438X2. The coefficient of determination value is 61.3% while the remaining 38.7% is influenced by other factors. Hypothesis testing obtained calculated F value > F table or (64.285 > 2.720). Keywords: Physical Work Environment, Training, Employee Performance